Clinicopathological Analysis of Bronchiolar Adenoma Lined Purely by Mucinous Luminal Cells - Guangjie Liao; Xinke Zhang (Case Reports in Pathology)
Bronchiolar adenoma (BA) is a rare lung tumor that has recently been clearly named, including the previous ciliated muconodular papillary tumor (CMPT) and the so-called nonclassical CMPT. The most prominent histological feature of BA is a double-layer cell structure composed of a continuous basal cell layer and a luminal cell layer. BA lined purely by mucinous luminal cells is very rare, and only one case has been reported in the English literature. This type of BA can easily be misdiagnosed as early mucinous adenocarcinoma. This article analyzes the clinicopathological characteristics of a newly discovered case of BA lined purely by mucinous luminal cells and fully integrated with the literatures.